Analisis Penerapan Literasi Keuangan Syariah pada Bisnis Trend Fashion Muslim di Indonesia - Hilal, Samsul; Ermawati, Liya; Fitri, Ainul (ITB AAS Indonesia Surakarta, 2023)
The development of Muslim fashion trends in Indonesia is currently very rapid, so it is necessary to manage finances in accordance with the teachings of Islamic sharia. This requires a greater understanding of sharia financial literacy. Sharia financial literacy is someone who understands and is able to apply knowledge about sharia finance and the ability to make financial decisions in accordance with financial principles and in accordance with Islamic rules. The aim of this research is to analyze the application of sharia financial literacy to the Muslim fashion trend business in Indonesia. This research method uses a descriptive and verification approach. The type of data used is primary data (observation, interviews and questionnaires). The research results show that the application of sharia financial literacy to the Muslim fashion trend business in Indonesia has gone well. In accordance with the results, to be able to manage finances, business people must understand and be able to apply good literacy about financial management. The better the business person's literacy understanding about sharia finance, the better they will be at managing finances. Apart from that, increasing knowledge and understanding regarding sharia financial literacy in the Muslim fashion trend business in Indonesia will encourage increased productivity in this business.